缺血性卒中患者血糖间隙与卒中复发的相关性 - Kang Yuan; Mengdi Xie; Huajuan Hou; Jingjing Chen; Xinyi Zhu; Huaiming Wang; Xiaohao Zhang; Yi Xie; Min Wu; Rui Liu; Xinfeng Liu (Journal of Diabetes, 2023)
Abstract Background Glycemic gap, as a novel index of acute glycemic excursion, is associated with poor prognosis of different diseases. This study aimed to explore the association of the glycemic gap with long‐term stroke recurrence in patients with ischemic stroke. Methods This study included patients with ischemic stroke from the Nanjing Stroke Registry Program. The glycemic gap was calculated by subtracting the estimated average blood glucose from the blood glucose at admission. Multivariable Cox proportional hazards regression analysis was performed to explore the association between the glycemic gap and the risk of stroke recurrence. The Bayesian hierarchical logistic regression model was used to estimate the effects of the glycemic gap on stroke recurrence stratified by diabetes mellitus and atrial fibrillation. Results Among 2734 enrolled patients, 381 (13.9%) patients experienced stroke recurrence during a median follow‐up of 3.02 years. In multivariate analysis, glycemic gap (high group vs. median group) was associated with significantly increased risk for stroke recurrence (adjusted hazard ratio, 1.488; 95% confidence interval, 1.140–1.942; p = .003) and had varying effects on stroke recurrence depending on atrial fibrillation. The restricted cubic spline curve showed a U‐shaped relationship between the glycemic gap and stroke recurrence (p = .046 for nonlinearity). Conclusion Our study found that the glycemic gap was significantly associated with stroke recurrence in patients with ischemic stroke. The glycemic gap was consistently associated with stroke recurrence across subgroups and had varying effects depending on atrial fibrillation.